Influence of Parental Behavior on Antisocial Behavior of Secondary School Students in Tetu Sub-County, Nyeri County, Kenya - Wambugu, Isabel; Karimi, Jane (Journal of Advanced Psychology, 2022)
Purpose: Research on modelling has shown that when parents are held in high esteem and are the main source of reinforcement, their child or children is/are more likely to model their behaviours. If a parent acts in a negative way, the child is more likely to emulate the negative behaviour. This study therefore aimed at investigating the influence of parental behaviour on the antisocial behaviour of students in Tetu Sub County, Nyeri County Kenya. Theoretical framework and Methodology: The study was guided by Bronfenbrenner ecological systems theory and fifth stage of psycho -social theory, further, the study adopted descriptive survey design. The target population was 2840 form four students. Proportionate and simple random sampling were used to select a sample of 352 students; one deputy principle and one teacher counsellor from all the sampled schools were also included in the study. Questionnaires and interview schedules were used to collect data. Test retest method was applied to test the reliability of the instruments while expert judgement was sought to ascertain the validity of the instruments. Descriptive and inferential statistics were used to analyse quantitative data with Pearson correlation testing the hypothesis for any relationship. Findings and Recommendation: From the quantitative analysis, the r (0.09) value is greater than zero thus indicating significant correlation between parental behaviour and antisocial behaviour of students in Tetu Sub County, Nyeri County -Kenya. Based on these findings, parental behaviour such as the use of drug abuse, alcohol abuse, parents being kind, attentive and caring to their children, parents offering guidance and counselling, absent parents due to business, and parents being single/separated or divorced had influence on antisocial behaviour among secondary school students. Qualitative analysis from interview schedules is in agreement with the quantitative analysis where the deputy teachers and teacher counsellors indicated that parental behaviours influence antisocial behaviours of students. Contributions to theory, practice and policy: Most parents may not be aware of the influence of their behaviours on the behaviour of their children, thus programmes to sensitize parents needs to be organised by ministry of education and respective schools. It is recommended that all stakeholders in education formulate a policy that governs parenting process at different stages of child development. Other factors such as economic problems, maternal depression, stress and domestic violence can lead to antisocial behaviours, there is need to develop strategies that will help parents to create a conducive environment for themselves and the children